Experimental Investigation on the Effect of Fused Deposition Modelling Parameters for HIPS Material by Experimental Design and MRO Techniques. Issue 1 (December 2020) - Mohammed Raffic, N; Ganesh Babu, K; Selvakumar, S; Radhakrishnan, S
Abstract: Fused Deposition Modelling (FDM) is one of the popular AM technique which utilizes thin thermoplastic filaments to create prototypes and end use products. The parts processed through FDM method have poor mechanical properties and surface quality characteristics in comparison to conventional manufactured products. Extensive research is underway in various parts of the world to bring an enhancement in mechanical properties and other related characteristics of the parts produced through FDM for making the process highly suitable to produce parts for diverse applications. The present work considers slice height, infill density, shell thickness and raster angle varied din three levels (34) to study their effects over output responses such as specimen weight, flexural strain and flexural strength. Taguchi's L9 orthogonal array is considered for preparing the experimental plan. Flexural testing is adopted for the evaluation of flexural strength. Grey Relational Analysis and Technique of Order Preference Similarity to the Ideal Solution methods have been adopted for multi response optimization of FDM parameters and the optimized parameter setting recommended have been validated through confirmation trials. The confirmation trail conducted has revealed that the setting recommended by TOPSIS A1B3C3D1 has shown higher flexural strength and slice height is found to be most significant factor. GRA method has recommended the combination A3B3C3D1 which shows lesser flexural strain and infill density is found to be significant from all the parameters considered.